Grow your own, with care - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
J J Kanjanga, director of the Lipangwe Organic Manure Demonstration Farm in Matale, Malawi, writes about 'LOMADEF s promotion of urban home gardening using organic farming principles. We would like to caution any agency seeing the sense of urban...